Intro to IoT pentesting - Lowrie, Daniel; Goodwin, Sophie (Packt Publishing, 2024)
The course begins by introducing you to the world of IoT and its significance in today's tech-driven society, emphasizing the importance of security in this interconnected environment. It covers the spectrum of IoT targets and the necessity of robust security measures to protect them. The course focuses on practical skills, including the use of hardware components like multimeters, TTL to USB, and JTAGulators, as well as software tools such as terminal emulators, Binwalk, and QEMU. You will learn about firmware analysis, including acquisition, extraction, and emulation, alongside techniques for exploiting embedded operating systems, network services, and IoT web applications. The course wraps up by guiding you through hands-on practices for identifying hardware vulnerabilities, automating UART pin identification, and gaining device access, ensuring you have the knowledge to perform comprehensive pentests on IoT devices.
Online resource; title from title details screen (O'Reilly, viewed March 19, 2024)
Keywords: Penetration testing (Computer security); Internet of things; Embedded Internet devices; Computer networks -- Security measures; Tests d'intrusion; Internet des objets; Internet intégré; Réseaux d'ordinateurs; Sécurité; Mesures; Instructional films; Nonfiction films; Internet videos; Films de formation; Films autres que de fiction; Vidéos sur Internet